KARAKTERISTIK KIMIA DAN ORGANOLEPTIK SET YOGURT DENGAN PENAMBAHAN VARIASI KOSENTRASI BUAH CAMPOLEH (Pouteria Campechiana ) - Yudistira, Wandi; Fizriani, Atia; Tubagus, Robi (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Campoleh fruit contains nutrients such as fibre, minerals and is high in vitamin C as an antioxidant. Yogurt set is a fermented milk product that has a thick texture and sour flavour. This study aims to determine the effect of the addition of campoleh fruit on the chemical and organoleptic characteristics of yogurt sets, and determine the best concentration of campoleh fruit based on SNI standards. This study used a complete randomised design method with the treatment of adding campoleh fruit concentrations of 10%, 15%, 20%, and 25%. The results of the analysis showed a significant effect on moisture content, ash content, protein, fat, lactic acid, vitamin C and colour. However, no significant effect showed the addition of campoleh fruit on colour, appearance, aroma and overall. The best concentration treatment of campoleh fruit addition to yogurt set is found in the campoleh fruit treatment of 25%, which has a moisture content of 73.84%, ash 0.92%, protein 4.64%, fat 1.85%, vitamin C 51.75 mg/100g, lactic acid 0.96%, colour 2.40, appearance 2.52, taste 2.52, aroma attribute 2.76 and overall 2.60.